The impact of different immunosuppressants and acute immune rejection on clinical outcomes in diverse solid organ transplant recipients - Wang, Zhihao; Liu, Zhenyu; Wu, Xia; Zeng, Xiong; Zhang, Tong; Li, Ziqiang (Frontiers in Immunology, 2026)
The success of solid organ transplantation (SOT) and the use of immunosuppressants provide patients with terminal conditions hope. Acute immune rejection (AR) in SOT patients, however, has become more noticeable. Our study examined the relationship between AR and patient survival in a variety of organ transplants, including liver, kidney, heart, lung, pancreas, intestine, combined heart–lung, and pancreas–kidney transplantations, using the Scientific Registry of Transplant Recipients (SRTR) database. Our research showed that AR universally reduces survival across all solid organ transplant types. Immunosuppressants exhibit organ-specific efficacy patterns, with divergent impacts on survival and AR risk. For instance, in liver transplants (LT), generic tacrolimus increased AR risk (OR: 1.31; 95% CI: 1.21–1.42), while AZA reduced it (OR: 0.52; 95% CI: 0.44–0.60). In kidney transplants (KT), tacrolimus increased AR risk (OR: 1.24; 95% CI: 1.2–1.28), whereas Cyclosporin reduced it (OR: 0.47; 95% CI: 0.43–0.52). Furthermore, the same immunosuppressant can have varying effects on survival across transplant types; MMF significantly increased the risk of death in LT, HT, LU, KT, HL, and PK patients, but reduced the risk of death in PT patients. Originator and generic immunosuppressants differentially influence survival outcomes and rejection incidence. For example, in heart transplantation (HT), originator cyclosporine improved survival, while generic cyclosporine (EON) was associated with decreased survival and increased AR risk. Overall, our research offers a thorough and methodical evaluation of how various immunosuppressants affect prognosis and how AR affects the survival of patients receiving different kinds of SOT.